2005
DOI: 10.1016/j.molbrainres.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment increases progenitor cell survival in the dentate gyrus following lateral fluid percussion injury

Abstract: Neurons in the hilus of the dentate gyrus are lost following a lateral fluid percussion injury. Environmental enrichment is known to increase neurogenesis in the dentate in intact rats, suggesting that it might also do so following fluid percussion injury, and potentially provide replacements for lost neurons. We report that 1 hour of daily environmental enrichment for 3 weeks increased the number of progenitor cells in the dentate following fluid percussion injury, but only on the ipsilesional side. In the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 80 publications
(118 reference statements)
0
43
0
1
Order By: Relevance
“…EE-induced neurogenesis may have enhanced the effect on learning and memory that was observed after 8-OH-DPAT. Increased expression of the synaptic proteins synaptophysin and PSD-95 [70], enhanced dendritic growth [58], and increased progenitor cell survival [30] may also contribute to the enhanced benefits by promoting plasticity-associated changes in learning and memory. The observed attenuation of hippocampal CA 3 cells in both the 8-OH-DPAT and EE treated groups suggests that neuroprotection may have also played a role in the observed benefits.…”
Section: Discussionmentioning
confidence: 99%
“…EE-induced neurogenesis may have enhanced the effect on learning and memory that was observed after 8-OH-DPAT. Increased expression of the synaptic proteins synaptophysin and PSD-95 [70], enhanced dendritic growth [58], and increased progenitor cell survival [30] may also contribute to the enhanced benefits by promoting plasticity-associated changes in learning and memory. The observed attenuation of hippocampal CA 3 cells in both the 8-OH-DPAT and EE treated groups suggests that neuroprotection may have also played a role in the observed benefits.…”
Section: Discussionmentioning
confidence: 99%
“…An increased dentate neurogenesis is also considered important for mediating some of the behavioral effects of antidepressants in major depressive disorders (Sahay and Hen, 2007). Studies have so far shown environmental enrichment induced association between increased dentate neurogenesis and improved functional outcome in aged mice (Kempermann et al, 2002), animals that underwent traumatic brain injury (Gaulke et al, 2005), transgenic mice exhibiting characteristics of Huntington's and Alzheimer's diseases (Lazic et al, 2006;Levi and Michaelson, 2007), and animals that underwent cranial irradiation (Fan et al, 2007).…”
Section: Modifications In Structure and Neurogenesismentioning
confidence: 99%
“…This paradigm has consistently shown improvements in behavioral and histological outcome after brain trauma and can therefore be considered a reasonable approach to preclinical rehabilitation. Importantly, the benefits conferred by EE span clinically-relevant models of experimental TBI, such as controlled cortical impact (CCI; Chen et al, 2005;de Witt et al, 2011;Hoffman et al, 2008;Kline et al, 2007Kline et al, ,2010Matter et al, 2011;Sozda et al, 2010) and fluid percussion (Hamm et al, 1996;Hicks et al, 2002;Gaulke et al, 2005;Giza et al, 2005;Maegele et al, 2005;Passineau et al, 2001). The second therapy in this combined treatment approach is the systemic administration of the serotonin 1A (5-HT 1A )-receptor agonist buspirone.…”
Section: Introductionmentioning
confidence: 99%